Idioma e identidad de género: is life satisfaction influenced by gendered language? - Rivas, Gabriela (My University, 2020)
This planned retrospective study will examine the relationship between first language spoken, gender identity, and life satisfaction among MacEwan students. The first language learned and fluently spoken by each subject will be classified as either gendered or non-gendered according to a set taxonomy. Subjects will be asked to self identify as having either a binary or non-binary gender identity. Finally, the Riverside Life Satisfaction Scale will be used to measure the subjects’ current life satisfaction. It is predicted that non-binary individuals who grew up speaking a non-gendered language will report higher levels of life satisfaction relative to non-binary individuals who grew up speaking a gendered language. The results may indicate that the degree of life satisfaction experienced by people who identify as non-binary may be adversely affected by the language they speak. If their primary language is highly gendered we predict a lower life satisfaction because of a mismatch between their gender identity and the language they use to describe themselves and the world around them.
Presented in absentia on April 27, 2020 at "Student Research Day" at MacEwan University in Edmonton, Alberta. (Conference cancelled)
Keywords: language; gender identity; life satisfaction